Drivers of archaeal ammonia-oxidizing communities in soil - Zhalnina, Kateryna; Dörr de Quadros, Patricia; A. O. Camargo, Flavio; Triplett, Eric W. (Frontiers in Microbiology, 2012)
Soil ammonia-oxidizing archaea (AOA) are highly abundant and play an important role in the nitrogen cycle. In addition, AOA have a significant impact on soil quality. AOA may cause nitrogen loss from soils, and the nitrate produced by AOA can lead to ground and surface water contamination, water eutrophication, and soil subsidence. The ammonia-oxidizing archaea discovered to date are classified in the phylum Thaumarchaeota. Only a few archaeal genomes are available in databases. As a result, AOA genes are not well annotated, and it is difficult to mine and identify archaeal genes within metagenomic libraries. Nevertheless, 16S rRNA and comparative analysis of ammonia monooxygenase sequences show that soils can vary greatly in the relative abundance of AOA. In some soils, AOA can comprise more than 10% of the total prokaryotic community. In other soils, AOA comprise less than 0.5% of the community. Many approaches have been used to measure the abundance and diversity of this group including DGGE, T-RFLP, q-PCR, and DNA sequencing. AOA have been studied across different soil types and various ecosystems from the Antarctic dry valleys to the tropical forests of South America to the soils near Mount Everest. Different studies have identified multiple soil factors that trigger the abundance of AOA. These factors include pH, concentration of available ammonia, organic matter content, moisture content, nitrogen content, clay content, as well as other triggers. Land use management appears to have a major effect on the abundance of AOA in soil, which may be the result of nitrogen fertilizer used in agricultural soils. This review summarizes the published results on this topic and suggests future work that will increase our understanding of how soil management and edaphoclimatic factors influence AOA.